2021
DOI: 10.3390/polym13132068
|View full text |Cite
|
Sign up to set email alerts
|

Printability Study of a Conductive Polyaniline/Acrylic Formulation for 3D Printing

Abstract: There is need for developing novel conductive polymers for Digital Light Processing (DLP) 3D printing. In this work, photorheology, in combination with Jacobs working curves, efficaciously predict the printability of polyaniline (PANI)/acrylate formulations with different contents of PANI and photoinitiator. The adjustment of the layer thickness according to cure depth values (Cd) allows printing of most formulations, except those with the highest gel point times determined by photorheology. In the working con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
48
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(58 citation statements)
references
References 50 publications
6
48
2
Order By: Relevance
“…In contrast with previous reports, [46,65] no significant differences are observed in the Young modulus of PANI composites compared to pristine acrylic resin within experimental error. However, the tensile strength and the elongation at break, neatly decreased as the amount of PANI increase, reducing ductility (both parameters decreased around 50% for 3.5 wt% PANI).…”
Section: Mechanical Propertiescontrasting
confidence: 99%
See 3 more Smart Citations
“…In contrast with previous reports, [46,65] no significant differences are observed in the Young modulus of PANI composites compared to pristine acrylic resin within experimental error. However, the tensile strength and the elongation at break, neatly decreased as the amount of PANI increase, reducing ductility (both parameters decreased around 50% for 3.5 wt% PANI).…”
Section: Mechanical Propertiescontrasting
confidence: 99%
“…These observations are in agreement with the different morphologies detected by SEM. Similarly, increasing the photoinitiator content from 4 to 10 wt% partly overcomes the competitive strong UV light absorption of PANI and increased the DBC% value of the composites with 3.5 wt% PANI, [46,60] in accordance with previous results.…”
Section: Uv-vis and Ftir Spectroscopysupporting
confidence: 90%
See 2 more Smart Citations
“…Both capable of printing complex structures with high resolution using photocurable polymers. 97 As illustration, Arias-Ferreiro et al 86,98 reported a photocured polyaniline (PANI)/acrylate polymer composite obtaining suitable electrical and electrochemical properties for SC. Despite SLA and DLP technologies are able to print flexible and customized devices, they do not allow the integration of different components in the same process, so they are not the most suitable obtaining technique for energy storage devices in the present.…”
Section: Other Am Techniques (Sla and Digital Light Processing)mentioning
confidence: 99%